PENDAMPINGAN MASYARAKAT BERBASIS INFORMATION TECHNOLOGY (IT) PADA PIMPINAN RANTING MUHAMMADIYAH BANGUNJIWO BARAT DI TENGAH PERSAINGAN MASYARAKAT EKONOMI ASEAN - Ali Maksum; Oki Wijaya (Universitas Ahmad Dahlan, 2021)
This community service aims to facilitate the economic sector for religious community organizations, especially towards the PRM Bangunjiwo Barat in the midst of competition from the ASEAN Economic Community (AEC). This community service is important because the Indonesian people generally lack awareness of the MEA. Empowerment in the economic sector, especially those based on micro, small and medium enterprises (SMEs) is very important when the flow of global capitalism into Indonesia is boundless and unstoppable. This is in line with the transformation of the theory of International Relations (IR) from traditional issues and high politics to issues based on non-traditional and community-based low politics, especially issues of development and human security. Human security issues include health security, food security, economic security, and others. The results of this community service have succeeded in facilitating partners and it is hoped that after the service they can increase their capacity in facing global competition, especially the AEC. Several important agendas were successfully implemented in the midst of the Covid-19 pandemic, for example video editing workshops, product photos, introduction to e-commerce including helping register products in the Grab-food application, and philanthropic activities